156 Influence of viscosity and fiber on nutrient digestibility and intestinal physiology in growing pigs. (30th November 2020) - Hung, Yuan-Tai; Zhu, Jinlong; Shurson, Gerald C; Saqui-Salces, Milena; Urriola, Pedro E
Abstract: Fiber is known for decreasing nutrient utilization in pigs. The addition of fiber alters diet viscosity, but our understanding of the effect of diet viscosity on nutrient digestibility is limited. This knowledge is necessary for improving dietary fiber utilization and when evaluating alternative feed ingredients. Thirty-six T-cannulated barrows (n = 6/treatment; initial BW = 26.5 ± 3.9 kg) were fed either corn-soybean meal (CSBM) basal diets or CSBM with 30% distillers dried grains with solubles as fiber source (CSBM+DDGS). The viscosity of diets were modified by using non-viscous cellulose (CEL), medium-viscosity carboxymethylcellulose (MCMC), or high-viscosity carboxymethylcellulose (HCMC) to assess viscosity effects on nutrient digestibility and intestinal physiology. After 29 d on diets, ileal digesta were collected to determine viscosity and apparent ileal digestibility (AID). Also, intestinal tissue and contents were harvested to determine morphometry, goblet cell quantitation, and digestive enzymatic activity. Data were analyzed using a linear mixed model with treatments as fixed effects and initial BW as a random effect. Results are shown in Table 1. No interactions were observed between viscosity and diets. Inclusion of MCMC and HCMC increased viscosity of supernatant and whole digesta compared with CEL. Increasing diet viscosity decreased AID of DM and CP in pigs fed MCMC and HCMC compared with pigs fed CEL, respectively. The AID of DM and CP were greater in CSBM than CSBM+DDGS. Inclusion of CMC increased crypt depth in the jejunum and goblet cell area in the ileum compared with pigs fed CEL regardless of basal diet fed. Digesta trypsin activity was not different among treatments, but inclusion of CMC increased amylase activity by 43% in jejunal digesta compared with CEL. The addition of DDGS reduced AID; however, viscosity affected intestinal morphology and function, suggesting that viscosity is the main characteristics of fiber affecting nutrient utilization of pigs.